A feasibility study in establishing "JPD's Kiosk" at CvSU-Rosario, Rosario, Cavite - Mabilog, Johnlyn M., author; Perez, Dexter L., author; Timpoc, Phia V., author; Evaneglista, Fedelita R., adviser (Rosario, Cavite : Cavite State University-CCAT Campus, 2006)
Thesis Abstract
A Feasibility Study (BSHRM)--Cavite State University-CCAT Campus, 2008.
Includes bibliographical references and appendices.
In English text.
Keywords: Food kiosk; Variety of Filipino dishes; Dine-in service; Take-out service; Customer preference; Quick service; On-the-go meals; Traditional cuisine; Feasibility study